Comparison of Artificial Intelligence and Human Motivation - Yoo, Seoyeon (Technium Social Sciences Journal, 2021)
According to Maslow's hierarchy of needs, humans act according to their needs. Humans also act with an interest in the internal process itself, rather than solely based on external rewards. Artificial intelligence, on the other hand, is trained through a large amount of data and neural network learning. Unlike humans who are greatly affected by emotions and various circumstances, AI is neutral and objective. With no clear limitations and vast potential for development. AI has been receiving a lot of attention. Many futurists say AI will replace humans in areas that we, in the past, couldn’t imagine machines doing the work. However, there are still areas where AI cannot replace humans. Metacognition to judge one's thoughts and creativity, the power to come up with new ideas, still remains in human domains that artificial intelligence has not been able to enter. This paper explores the reinforcement of humans and AI and explores the original human realm. Furthermore, understanding the original human domain can suggest developing human competitiveness.